2020
DOI: 10.1038/s41541-020-00236-w
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a neutralizing mAb H16.001, a potent candidate for a common potency assay for various HPV16 VLPs

Abstract: With more human papillomavirus (HPV) virus-like particle (VLP) vaccines to hit the market in future, a monoclonal antibody (mAb) with preferably comparable reactivity against vaccines from different expression systems and bioprocesses is urgently needed for the potency characterization. Among all mAbs against HPV16 collected, rabbit mAb H16.001 is potently neutralizing with the highest affinity, recognizes an immune-dominant epitope, and can comparably react with HPV16 vaccines from various sources. Cryo-elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Previously, reconstructions of papillomaviruses with full icosahedral symmetry imposed have produced maps limited to modest resolution; however, recently subparticle reconstruction approaches have been successfully used to obtain high resolution [ 16 , 17 , 36 ]. Consistent with this finding, we found that for the native papillomavirus the icosahedrally enforced reconstruction did not advance beyond 4.4 Å resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, reconstructions of papillomaviruses with full icosahedral symmetry imposed have produced maps limited to modest resolution; however, recently subparticle reconstruction approaches have been successfully used to obtain high resolution [ 16 , 17 , 36 ]. Consistent with this finding, we found that for the native papillomavirus the icosahedrally enforced reconstruction did not advance beyond 4.4 Å resolution.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the generality of flexibility-based method presented here, protein flexibility's influence on conserved human papillomavirus [16] (HPV) epitopes was examined. Benchmarking was performed against two highly conserved (mean residue evolutionary rate of 1.52) [25] HPV epitopes (PDB IDs: 7CN2 [54], 3J8Z [55]) out of eight structurally characterized HPV epitopes (evolutionary rate range of 1.18-2.47). Like flaviviruses, linear combination of HPV isolated and VLP protein flexibility (using weights which minimized the root-meansquare difference between the two flexibility profiles) performed with the strongest capacity (of all metrics examined) to pinpoint conserved HPV epitope residues (a PRAUC mean 0.21 above the value of no discrimination, 0.07) (Table 3).…”
Section: Plos Onementioning
confidence: 99%
“…Of the seven highly conserved epitopes, 14% were associated with ZIKV, 0% were associated with dengue virus serotype 1, 14% were associated with dengue virus serotype 2, 14% were associated with dengue virus serotype 3, 29% were associated with dengue virus serotype 4, ROCAUC and PRAUC values calculated against two highly conserved HPV epitopes [54,55] are shown for the linear difference of isolated and VLP RMSF (fmon-fvlp),…”
Section: Conserved Epitope Organization and Epitope Discovery Demonst...mentioning
confidence: 99%
See 2 more Smart Citations